Anti-diabetic, anti-inflammatory and molecular docking studies of benzofuran derivatives as potential α-glucosidase and lipoxygenase inhibitors - E.N. Agbo; Redolf.S. Segodi; N.J. Gumede; K.W. Poopedi; T.C. Leboho; R.M. Mampa; W. Nxumalo (Results in Chemistry, 2025)
Sonogashira cross-coupling of 5-bromo-2-hydroxy-3-iodoacetophenone and subsequent Suzuki-Miyaura cross-coupling of the 1-(5-bromo)-2–substituted furan-7-yl) ethanones afforded series of novel 1-(5-(4-aryl)-2–substituted furan-7-yl) ethanone derivatives. The potential anti-inflammatory and anti-diabetic properties of the prepared compounds were evaluated against lipoxygenase (LOX-15) and α-glucosidase enzymes, respectively. Besides compounds 2b and 2c with IC50 values of 8.8 μM and 11.2 μM against α-glucosidase and LOX-1, respectively, the 1-(5-bromo)-2–substituted furan-7-yl) ethanones were found to be poorly inhibitors of both enzymes. On the other hand, compounds 3j (IC50 = 8.0 μM) and 3l (IC50 = 5.3 μM) exhibited significant inhibitory activity against LOX-15 and α-glucosidase, respectively. Cytotoxicity of the most active compound was evaluated against Raw 264.7 macrophages. Molecular docking and MDS studies of the most active compounds against α-glucosidase enzyme have revealed that the structure-activity relationship (SAR) of the 1-(5-(4-aryl)-2–substituted furan-7-yl) ethanone analogues indicates a water-mediated hydrogen bond between ASP232 and ARG552 influences the activity of these analogues. Furthermore, hydrophobic interactions facilitated by TRP329, PHE364, TRP432, SER474, PHE476, and PHEPHE601 are important for the enzyme-ligand recognition of these compounds.